TOXICOLOGICAL EFFECT OF LOCAL/NATURAL INSECTICIDES: SEEDS OF AZADIRACHTA INDICA, PEELS OF CITRUS SINENSIS AND THEIR COMBINATION ON LIVER ENZYMES - Bello, Aliyu M; Wudil, Al'hassan M; Muhammad, Murtala; Muhammad, Ibrahim Ahmad; Muhammad, Mustapha Garba; Al-Khatib, Ahed J (European Scientific Journal, ESJ, 2014)
Natural plant products and materials have been used by local people as insecticides to control insects such as mosquito. Among the most notable plants having such insecticidal properties are Azadirachta indica (neem) and Citrus sinensis (sweet orange). The leaves of these plants have been immensely studied and well known for their medicinal value. Whereas, the seeds of Azadirachta indica and peels of Citrus sinensis were mostly known for their insecticidal properties and have been found to be hepatotoxic. Therefore, this study is aimed at investigating the toxicological effects of these plant materials on the liver. The treatment involved exposing three groups of white albino rats (Rattus novergicus) to the smoke of dried and grinded seeds of Azadirachta indica, peels of Citrus sinensis and their combination at different duration of one hour and two hours for each group respectively. The first group (Group A) was not exposed to any of the natural insecticides and was fed normal diet and water, and therefore served as control. After four weeks of the treatment, all the rats were sacrificed and the liver enzymes AST, ALT and ALP were assayed. The serum levels of AST, ALT and ALP for the rats that were treated have been found to significantly increase (at p<0.05) when compared to the control. Therefore, the result of this study revealed that these natural insecticides have significant effect on the serum level of liver enzymes. However, the duration of exposure increases the severity of the effect. This implies that these plant materials could cause liver injury and as such they are toxic to the liver at the duration of exposure studied.